Simultaneous Sensitive Determination of δ13C, δ18O, and δ17O in Human Breath CO2 Based on ICL Direct Absorption Spectroscopy - Ligang Shao; Jiaoxu Mei; Jiajin Chen; Tu Tan; Guishi Wang; Kun Liu; Xiaoming Gao (Sensors, 2022)
Previous research revealed that isotopes 13C and 18O of exhaled CO2 have the potential link with Helicobacter pylori; however, the 17O isotope has received very little attention. We developed a sensitive spectroscopic sensor for simultaneous δ13C, δ18O, and δ17O analysis of human breath CO2 based on mid-infrared laser direct absorption spectroscopy with an interband cascade laser (ICL) at 4.33 μm. There was a gas cell with a small volume of less than 5 mL, and the pressure in the gas cell was precisely controlled with a standard deviation of 0.0035 Torr. Moreover, real-time breath sampling and batch operation were achieved in gas inlets. The theoretical drifts for δ13C, δ18O, and δ17O measurement caused by temperature were minimized to 0.017‰, 0.024‰, and 0.021‰, respectively, thanks to the precise temperature control with a standard deviation of 0.0013 °C. After absolute temperature correction, the error between the system responded δ-value and the reference is less than 0.3‰. According to Allan variance analysis, the system precisions for δ13C, δ18O, and δ17O were 0.12‰, 0.18‰, and 0.47‰, respectively, at 1 s integration time, which were close to the real-time measurement errors of six repeated exhalations.